Communication Strategies in Islamic Da'wah for Strengthening the Spirituality of Muslim Communities in the Digital Era - Madu Trisna Devi; Anis Dwi Winarsih; Karlina Karadila Yustisia (KOMUNITAS, 2026)
The rapid development of digital media has transformed da'wah communication into a more interactive and influential process for strengthening Muslim spirituality. This study examines da'wah communication strategies through illocutionary speech acts in Ustadz Hanan Attaki's sermon Learning to Be Calm Even When There Are Many Problems. Using qualitative content analysis, the sermon transcript was analyzed through the interactive model of Miles, Huberman, and Saldaña, integrating Searle's illocutionary speech act theory with da'wah communication theory. The findings reveal four dominant strategies persuasive, empathetic, reflective, and motivational expressed through assertive, directive, expressive, and commissive speech acts. These strategies promote spiritual awareness, emotional engagement, self-reflection, and religious commitment. The study concludes that illocutionary speech acts serve as strategic communication tools that enhance the effectiveness of humanistic and transformative digital da'wah in strengthening Muslim spirituality within contemporary digital communication contexts.